The role of psychological flexibility on headache severity following mild traumatic brain injury : a thesis presented in partial fulfilment of the requirements for the degree of Master of the Arts in Psychology at Massey University, Wellington, New Zealand - Johnston, Lydia (Massey University, 2022)
Several studies have confirmed there is a relationship between psychological factors and the experience of ongoing symptoms following a mild traumatic brain injury (mTBI). However, there is mixed evidence about which psychological factors. One emerging factor is psychological flexibility, a concept with theoretical foundations and which can be increased through Acceptance and Commitment Therapy (ACT). While other studies have looked at psychological flexibility and overall symptoms, there is benefit in looking more specifically at one symptom. One of the most prominent symptoms following mTBI are headaches, however there is not, currently, a complete understanding of what factors may lead to the experience and severity of headaches following an mTBI. This study obtained data from 149 participants through concussion clinics throughout the North Island of New Zealand at clinic intake, and at six months follow up 100 participants continued to participate. We measured psychological flexibility through the AAQ-ABI(RA), psychological distress through the DASS-21, and headaches through one item on the RPQ. The findings from these individuals supported all our hypotheses. Specifically, we found significant associations through multiple regression analysis between lower psychological flexibility and higher severity headaches at two time points: baseline and six months follow-up. We also found an association between psychological flexibility at baseline and headaches at six months follow-up. We also completed mediation analysis which found a significant influence of psychological flexibility on the relationship between psychological distress and headache severity at the same time periods. These results indicate that psychological flexibility may be a key mechanism in the experience of headaches after mTBI. Our results suggest that targeting psychological flexibility through ACT may help to improve the severity of headaches after mTBI.
Figure 5 was removed for copyright reasons. Figure 4 is re-used under a Creative Commons Attribution-ShareAlike 4.0 International (CC BY-SA 4.0) license.
Keywords: psychological flexibility; mild traumatic brain injury (mTBI); headaches; post concussive symptoms; psychological distress; 520304 Health psychology